Skuteczność stosowania nowoczesnych form wynagradzania pracowników w polskich organizacjach - Gruszczyńska-Malec, Grażyna; Rutkowska, Monika (Effectiveness of New Compensation Forms in Polish Enterprises, 2006)
In the article new compensation forms are presented. The authors first discuss their propriety and effectiveness, then in the second part they analyse empirical results related to application of. new compensation forms in Polish enterprises and employees' opinion on them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 295-304